Maternal plasma soluble TRAIL is decreased in preeclampsia. (February 2014) - Chaemsaithong, Piya; Chaiworapongsa, Tinnakorn; Romero, Roberto; Korzeniewski, Steven J.; Stampalija, Tamara; Than, Nandor Gabor; Dong, Zhong; Miranda, Jezid; Yeo, Lami; Hassan, Sonia S.
Abstract Objective: Preeclampsia (PE) is characterized by systemic intravascular inflammation. Women who develop PE are at an increased risk for cardiovascular disease in later life. Tumor necrosis factor related apoptosis-inducing ligand (TRAIL) has anti-atherosclerotic effects in endothelial cells and can mediate neutrophil apoptosis. Low soluble TRAIL (sTRAIL) and high C-reactive protein (CRP) concentrations are associated with an increased risk of future cardiovascular disease in non-pregnant individuals. The aim of this study was to determine whether maternal plasma concentrations of sTRAIL and CRP differ between women with PE and those with uncomplicated pregnancies. Method: This cross-sectional study included women with an uncomplicated pregnancy (n = 93) and those with PE (n = 52). Maternal plasma concentrations of sTRAIL and CRP concentrations were determined by ELISA. Results: 1) The median plasma sTRAIL concentration (pg/mL) was significantly lower and the median plasma CRP concentration was significantly higher in women with PE than in those with an uncomplicated pregnancy (25.55 versus 29.17; p = 0.03 and 8.0 versus 4.1; p = 0.001, respectively); 2) the median plasma concentration sTRAIL/CRP ratio was two-fold lower in women with PE than in those with an uncomplicated pregnancy (p < 0.001); and 3) women with plasma sTRAIL and CRP ratio in the lowest quartile were 8 times more likely to have PE than women with concentrations in the upper three quartiles (OR 8.9; 95% CI: 2.8–27.8). Conclusion: Maternal plasma sTRAIL concentrations are lower (while those of CRP are higher) in women with PE than in those with uncomplicated pregnancies. These findings are consistent with the evidence of intravascular inflammation in this disorder.